2022
DOI: 10.3389/fnut.2021.833666
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Probiotics in Children and Adolescents With Atopic Dermatitis: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: ObjectiveTo evaluate the clinical efficacy of a mixture of probiotics (Lactobacillus and Bifidobacterium) in children and adolescents with atopic dermatitis (AD) and the effects on sensitization, inflammation, and immunological tolerance.MethodsIn this double-blind, randomized, placebo-controlled clinical trial, we enrolled 60 patients aged between 6 months and 19 years with mild, moderate, or severe AD, according to the criteria proposed by Hanifin and Rajka. Patients were stratified to receive one gram per d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
10
0
3
Order By: Relevance
“…While enteral probiotics have been studied in detail [14][15][16][17][18][19] and they may include possibilities for primary prevention, the role of topical probiotics in the treatment of active AD remains uncertain. There have only been a few studies which have investigated the use of topical probiotics in AD and further evidence is needed to determine their efficacy, optimal dosing, and specific bacterial strains needed for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While enteral probiotics have been studied in detail [14][15][16][17][18][19] and they may include possibilities for primary prevention, the role of topical probiotics in the treatment of active AD remains uncertain. There have only been a few studies which have investigated the use of topical probiotics in AD and further evidence is needed to determine their efficacy, optimal dosing, and specific bacterial strains needed for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Os estudos foram realizados em distintas faixas etárias, que compreende de 0 a 19 anos de idade, sendo que o uso de probióticos foi avaliado de forma direta, através do tratamento de pacientes com dermatite atópica, em diferentes estágiosleve, moderado ou grave (IBÁÑEZ et al, 2018;AHN et al, 2020;JEONG et al, 2020;CUKROSWSKA et al, 2021;ANDRADE et al, 2022;CARUCCI et al, 2022), de forma preventiva por suplementação precoce em recém-nascidos (CABANA et al, 2017;) e, indiretamente, a partir de suplementação de gestantes, antes do parto e, após o parto, a partir da amamentação (WICKENS et al, 2018).…”
Section: Discussionunclassified
“…Após a análise de diversos trabalhos (KALLIOMÄKI et al, 2001;VILJANEN et al, 2004;FÖLSTER-HOLST et al, 2006;GRÜBER et al, 2007), Cukroswska e colaboradores ( 2021 Tratando-se do gênero Lactobacillus sp., a espécie L. rhamnosus foi estudada em sete trabalhos, tanto de forma isolada (CABANA et al, 2017;JEONG et al, 2020;CARUCCI al., 2022), quanto de forma simbiótica com mais de uma bactéria (IBÁÑEZ et al, 2018;CUKROWSKA et al, 2021;ANDRADE et al, 2022;WICKENS et al, 2022)…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Depending on the source of bacteria, multiple factors could contribute to shaping the milk microbiota ( Andreas et al, 2015 ; Zimmermann and Curtis, 2020 ). On the one hand, the microbial composition and diversity of breast milk may be influenced by maternal characteristics, including ethnicity ( Deschasaux et al, 2018 ; Xu et al, 2020 ; Shafiee et al, 2022 ), pregnancy age, body mass index (BMI) ( Cabrera-Rubio et al, 2012 ), mode of delivery ( Cabrera-Rubio et al, 2012 ), parity, and intake of intrapartum antibiotics or probiotics ( de Andrade et al, 2021 ). Meanwhile, several studies have reported differences in the microbiota composition of HM in different geographic locations, just as they do in the human skin metagenome ( Gupta et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%